Oomycetes associated with Prunus serotina persist in soil after tree harvest. (October 2021) - Esch, Clarice M.; Medina-Mora, Carmen M.; Kobe, Richard K.; Sakalidis, Monique L.
Abstract: Soil-borne pathogens can shape forest communities by lowering seedling survivorship. Many soil pathogens can persist long-term as survival spores, but how long pathogens outlive tree hosts in gap soils and whether they continue to affect seedling survival is uncertain. We studied the presence of oomycetes and evaluated seedling performance in soils near live Prunus serotina trees, and 0.5 and 1.5-y-old stumps. We isolated five species of oomycetes from soils, two of which were pathogenic ( Pythium intermedium and Pythium irregulare ) to Prunus serotina . There was a non-significant 10.5% increase in conspecific seedling survival in stumps versus live trees, and pathogens were present in soils of all stump ages. The continued presence of pathogens of Prunus serotina in gap soils demonstrates the potential for impacts on conspecific regeneration after tree death, though the slight improvement in survival suggests that these effects may weaken with time.